Hepatitis B Virus (HBV) Replication During Tenofovir Therapy Is Frequent in Human Immunodeficiency Virus/HBV Coinfection. (15th October 2022) - Hofmann, Eveline; Surial, Bernard; Boillat-Blanco, Noémie; Günthard, Huldrych F; Stöckle, Marcel; Bernasconi, Enos; Schmid, Patrick; Calmy, Alexandra; Suter-Riniker, Franziska; Rauch, Andri; Wandeler, Gilles; Béguelin, Charles; et al.
Abstract: In the Swiss HIV Cohort Study, 61 of 222 (27%) HIV–suppressed persons with chronic hepatitis B virus (HBV) infection had HBV replication after 2 years on tenofovir, of whom 77% were suppressed thereafter. Self-reported adherence to therapy and HBV viral load at tenofovir initiation were predictors of persistent replication.